2022
DOI: 10.1155/2022/2810379
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Revealing the Longevity Code of Humans with up to Extreme Longevity in Guangxi Based on Physical Examination Indicators and Personalized Biomarkers of Aging

Abstract: Background. The pursuit of health and longevity is the eternal theme of humanity. Guangxi has a remarkable phenomenon of longevity in long-lived regions and ranks with the highest number of longevity villages in China, thus providing a natural advantage for health longevity research. Methods. In this study, we selected 117 natives of a longevity area in Guangxi, covering a large age range (38-118 years old) as subjects to measure peripheral leukocyte telomere length (LTL). Nineteen physical examination indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Bama, Donglan, and Fengshan are the three most famous longevity populations in Guangxi, and which prevalence of the three counties was 35.6, 31.4, and 28.5 centenarians/100,000 citizens in 2019, respectively ( 13 ). In our previous study, 66.7% of the population aged >60 in this longevity area had SBP≥140 mmHg ( 22 ). This co-existence of longevity and hypertension is well worth investigating.…”
Section: Introductionmentioning
confidence: 82%
“…Bama, Donglan, and Fengshan are the three most famous longevity populations in Guangxi, and which prevalence of the three counties was 35.6, 31.4, and 28.5 centenarians/100,000 citizens in 2019, respectively ( 13 ). In our previous study, 66.7% of the population aged >60 in this longevity area had SBP≥140 mmHg ( 22 ). This co-existence of longevity and hypertension is well worth investigating.…”
Section: Introductionmentioning
confidence: 82%
“…Bama County in Guangxi is a world-renowned longevity town, where the phenomenon of longevity is highlighted [ 1 ]. Our research team conducted a lot of research on the dietary characteristics of the longevity population in the early stage, and found that the traditional diet in the Bama area is mainly based on the food intake of plant foods, such as coarse grains (Taro, hemp, corn, cassava, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an examination of physical health indicators in subjects of the longevity regions of Hechi by our research team revealed that long-lived older adults, especially centenarians, had a good hepatic function, lower lipid levels, and lower levels of inflammation. This makes it more meaningful to explore the health and longevity phenomenon in Guangxi from the perspective of metabolomics in combination with dietary characteristics [16]. In the present study, diet-related signature metabolites of longevity were evaluated through the analysis of plasma metabolites and dietary characteristics of the longevity population in the Hechi region.…”
Section: Introductionmentioning
confidence: 99%